TANTANGAN DIGITAL DAN IMAN GEN Z: SEBUAH PENDEKATAN PENDAMPINGAN MENTORING COMPANIONSHIP - Lia Rosalia Sianturi; Wilson Simbolon (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Mentoring companionship, which is grounded in trust, empathy, and personal connection, plays an important role in supporting students’ academic and career development. However, the characteristics of Generation Z as digital natives have transformed communication patterns and social interactions, creating challenges for traditional mentoring practices. This condition highlights the need for a deeper understanding of the barriers to establishing effective mentoring relationships in the digital era. This study aims to systematically analyze and synthesize the main challenges in implementing mentoring companionship for Generation Z students based on existing academic literature. The study employed a qualitative Systematic Literature Review (SLR) method. The research stages included article identification, screening based on inclusion and exclusion criteria, eligibility assessment, and thematic analysis and synthesis of the selected articles. The findings indicate that the major challenges include intergenerational communication gaps, reduced quality of interpersonal interactions due to the dominance of digital communication, difficulties in building trust, differences in expectations between mentors and mentees, and the need for more flexible mentoring approaches. In addition, Generation Z students tend to prefer mentoring relationships that are collaborative, personalized, and responsive to their needs. The study concludes that the digital era requires a shift in mentoring paradigms from hierarchical approaches toward more relational, adaptive, and technology-supported models to enhance the effectiveness of mentoring companionship for Generation Z students. ABSTRAK Mentoring companionship yang didasarkan pada kepercayaan, empati, dan koneksi personal berperan penting dalam mendukung perkembangan akademik dan karier mahasiswa. Namun, karakteristik Generasi Z sebagai digital native telah mengubah pola komunikasi dan interaksi sosial, sehingga menimbulkan tantangan bagi praktik mentoring tradisional. Kondisi ini menuntut adanya pemahaman yang lebih mendalam mengenai hambatan dalam membangun hubungan mentoring yang efektif di era digital. Penelitian ini bertujuan untuk menganalisis dan mensintesis secara sistematis tantangan utama dalam penerapan mentoring companionship bagi mahasiswa Generasi Z berdasarkan literatur akademik yang tersedia. Penelitian menggunakan metode Systematic Literature Review (SLR) dengan pendekatan kualitatif. Tahapan penelitian meliputi identifikasi artikel, penyaringan berdasarkan kriteria inklusi dan eksklusi, penilaian kelayakan, serta analisis dan sintesis tematik terhadap artikel yang terpilih. Hasil kajian menunjukkan bahwa tantangan utama meliputi kesenjangan komunikasi antar generasi, rendahnya kualitas interaksi interpersonal akibat dominasi komunikasi digital, kesulitan membangun kepercayaan, perbedaan ekspektasi antara mentor dan mentee, serta kebutuhan akan pendampingan yang lebih fleksibel. Selain itu, mahasiswa Generasi Z cenderung mengharapkan hubungan mentoring yang kolaboratif, personal, dan responsif terhadap kebutuhan mereka. Simpulan penelitian menunjukkan bahwa era digital memerlukan pergeseran paradigma mentoring dari pendekatan hierarkis menuju model yang lebih relasional, adaptif, dan berbasis teknologi untuk meningkatkan efektivitas mentoring companionship bagi mahasiswa Generasi Z.